Poststroke Trajectories: The Process of Recovery Over the Longer Term Following Stroke. (11th September 2017) - Hawkins, Rebecca J.; Jowett, Adam; Godfrey, Mary; Mellish, Kirste; Young, John; Farrin, Amanda; Holloway, Ivana; Hewison, Jenny; Forster, Anne
We adopted a grounded theory approach to explore the process of recovery experienced by stroke survivors over the longer term who were living in the community in the United Kingdom, and the interacting factors that are understood to have shaped their recovery trajectories. We used a combination of qualitative methods. From the accounts of 22 purposively sampled stroke survivors, four different recovery trajectories were evident: (a) meaningful recovery, (b) cycles of recovery and decline, (c) ongoing disruption, (d) gradual, ongoing decline. Building on the concept of the illness trajectory, our findings demonstrate how multiple, interacting factors shape the process and meaning of recovery over time. Such factors included conception of recovery and meanings given to the changing self, the meanings and consequences of health and illness experiences across the life course, loss, sense of agency, and enacting relationships. Awareness of the process of recovery will help professionals better support stroke survivors.